Using phytoestrogens as aprophylaxis against irregular uterine bleeding possibly occurring while using Depot-medroxyprogesterone acetate (DMPA) as a contraceptive method - El Fattah, Iman Ali Abd (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: High-dose progestogen - only contraceptives, such as injectable DMPA, inhibit follicular development and prevent ovulation as their primary mechanism of action. Inhibition of ovarian function during DMPA use causes the endometrium to become thin and atrophic. These changes in the endometrium in the first months of use results in irregular or unpredictable bleeding or spotting, or rarely, heavy or continuous bleeding .Phytoestrogens are plant-derived xeno-estrogens functioning as the primary female sex hormone not generated within the endocrine system but consumed by eating phytoestrogenic plants. Also called “dietary estrogens”, they are a diverse group of naturally occurring non-steroidal plant compounds that, because of their structural similarity with estradiol (17-β-estradiol), have the ability to cause estrogenic or/and antiestrogenic effects through binding to estrogen receptors. The management of women who present with unscheduled bleeding while using hormonal contraception is challenging. Although numerous research studies have attempted to investigate preventative and therapeutic treatments for women using hormonal contraception with unscheduled bleeding, none are of sufficient quality to guide management in clinical practice usefully. In this study we are testing the ability of phytoestrogens to prevent the break-through bleeding that can occur during the use of depot medroxy-progesterone acetate as a contraceptive. Methods: Fifty cases of depot provera users are selected and divided into two groups: group I: 25 cases will start the injection alone. Group II: 25 cases will start the injection with using regular daily phytoestrogen. All cases are followed up for the first six months after the injection for the occurrence of break-through bleeding, and the endometrial thickness using the trans-vaginal ultrasonography. Results: There was a statistically significant difference in the endometrial thickness between group receiving depot provera alone and the group receiving both depot provera and phytoestrogen. Conclusions: We can use phytoestrogens to decrease DMPA-associated vaginal bleeding.